Location - allocation model for new waste disposal location in Perlis / Nurul Syahirah Misbi - Misbi, Nurul Syahirah (2018)
The shortage of waste disposal location in urban area always be a critical issue and problem due to the extremely growth population and urbanization that lead the poor planning, management of municipal solid waste (MSW) and environmental impact in most developing state especially state of Perlis. The increasing migration process since as well as human desire to live in cities causes the amount of solid waste generated increased every day. This research is to examine the suitable area for waste disposal location in Perlis and adopt the Geographical Information System (GIS) and location-allocation model. Geographical Information System (GIS) tool was used to find the new suitable area for waste disposal location at Perlis. The optimum location waste disposal location was assessed according to the static criteria which is the parameters and optimum distance that involving with the distance from facilities to the demand point that was referring to the results of meetings and discussions with the SWCorp and planning guidelines prepared by the Town Planning Department of the Peninsular Malaysia. In conclusion, the result of this research also showed the new waste disposal location and this research would deal with how Geographical Information System can be used as a decision support tool for assist in determining appropriate waste disposal location in solid waste management.